Predicting Completion: The Road to Informed Study Decisions in Higher Online Education - Delnoij, Laurie; Janssen, Jose; Dirkx, Kim; Gijselaers, Hieronymus; de Groot, Renate H.; Neroni, Joyce; de Bie, Marion; Martens, Rob (Frontiers in Education, 2021)
Non-completion is an ongoing concern in higher education, and even more so in higher online education. One way to address this problem is to take initiatives prior to student enrolment, enabling informed decision making. In line with this, an institution for open higher online education seeks to develop a (non-committal) online self-assessment for prospective students. To identify variables (tests) to be included in this self-assessment, the present study aims at validating variables – previously identified as ‘predictive of completion in higher education and open to intervention before enrolment’ – within the current higher online education context. Results of correlational analyses indicate that the following modifiable variables are relevant to include: hours planned to study, employment hours, study intention, discipline, discipline confidence, basic mathematical skills, and social support. Based on a sensitivity cut-off of 95% (to minimize false negatives) about 13% of the actual non-completers could be identified correctly. Implications for future development of the self-assessment are discussed.